Structural and Kinetic Analyses of the Protease from an Amprenavir-Resistant Human Immunodeficiency Virus Type 1 Mutant Rendered Resistant to Saquinavir and Resensitized to Amprenavir - Markland, W. (American Society for Microbiology, 2000)
Recent drug regimens have had much success in the treatment of human immunodeficiency virus (HIV)-infected individuals; however, the incidence of resistance to such drugs has become a problem that is likely to increase in importance with long-term therapy of this chronic illness. An analysis and understanding of the molecular interactions between the drug(s) and the mutated viral target(s) is crucial for further progress in the field of AIDS therapy. The protease inhibitor amprenavir (APV) generates a signature set of HIV type 1 (HIV-1) protease mutations associated with in vitro resistance (M46I/L, I47V, and I50V [triple mutant]). Passage of the triple-mutant APV-resistant HIV-1 strain in MT4 cells, in the presence of increasing concentrations of saquinavir (SQV), gave rise to a new variant containing M46I, G48V, I50V, and I84L mutations in the protease and a resulting phenotype that was resistant to SQV and, unexpectedly, resensitized to APV. This phenotype was consistent with a subsequent kinetic analysis of the mutant protease, together with X-ray crystallographic analysis and computational modeling which elucidated the structural basis of these observations. The switch in protease inhibitor sensitivities resulted from (i) the I50V mutation, which reduced the area of contact with APV and SQV; (ii) the compensating I84L mutation, which improved hydrophobic packing with APV; and (iii) the G-to-V mutation at residue 48, which introduced steric repulsion with the P3 group of SQV. This analysis establishes the fine detail necessary for understanding the loss of protease binding for SQV in the quadruple mutant and gain in binding for APV, demonstrating the powerful combination of virology, molecular biology, enzymology, and protein structural and modeling studies in the elucidation and understanding of viral drug resistance.